Low cost NodeMcu based development water rocket measurement system applied to STEM education - Andi Susilo; Yasmiati Yasmiati; Ahmad Apandi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Water rockets have become one of learning tools for STEM Education in schools. Generally water rockets make in school activity have no parachute load, altitude, and velocity measurement. Rocket can go any direction and also will cause hard collision to the ground that break the high speed rocket. It will take time and need more cost to make a new one for students. This study propose the low cost NodeMcu based water rocket measurement system to solve the problem. Altitude and velocity measurement are added and deployment system to release the parachute to make water rocket fall to the ground smoothly. Smartphone application used to monitor altitude and velocity of water rocket. Variables consist of water volume and air pressure. Five experiments had been conducted and recorded. The result found that the system could calculate Altitude, Velocity, and Deployment System also could release the parachute automatically in Coasting Descent position.